Therapeutic Potential of Peucedanum japonicum Thunb. and Its Active Components in a Delayed Corneal Wound Healing Model Following Blue Light Irradiation-Induced Oxidative Stress - Wan Seok Kang; Eun Kim; Hakjoon Choi; Ki Hoon Lee; Kyeong Jo Kim; Dosung Lim; Su-young Choi; Youngbae Kim; Seon ah Son; Jin Seok Kim; Sunoh Kim (MDPI AG, 2023)
Blue light is reported to be harmful to eyes by inducing reactive oxygen species (ROS). Herein, the roles of Peucedanum japonicum Thunb. leaf extract (PJE) in corneal wound healing under blue light irradiation are investigated. Blue-light-irradiated human corneal epithelial cells (HCECs) show increased intracellular ROS levels and delayed wound healing without a change in survival, and these effects are reversed by PJE treatment. In acute toxicity tests, a single oral administration of PJE (5000 mg/kg) does not induce any signs of clinical toxicity or body weight changes for 15 days post-administration. Rats with OD (oculus dexter, right eye) corneal wounds are divided into seven treatment groups: NL (nonwounded OS (oculus sinister, left eye)), NR (wounded OD), BL (wounded OD + blue light (BL)), and PJE (BL + 25, 50, 100, 200 mg/kg). Blue-light-induced delayed wound healing is dose-dependently recovered by orally administering PJE once daily starting 5 days before wound generation. The reduced tear volume in both eyes in the BL group is also restored by PJE. Forty-eight hours after wound generation, the numbers of inflammatory and apoptotic cells and the expression levels of interleukin-6 (IL-6) largely increase in the BL group, but these values return to almost normal after PJE treatment. The key components of PJE, identified by high-performance liquid chromatography (HPLC) fractionation, are CA, neochlorogenic acid (NCA), and cryptochlorogenic acid (CCA). Each CA isomer effectively reverses the delayed wound healing and excessive ROS production, and their mixture synergistically enhances these effects. The expression of messenger RNAs (mRNAs) related to ROS, such as SOD1, CAT, GPX1, GSTM1, GSTP1, HO-1, and TRXR1, is significantly upregulated by PJE, its components, and the component mixture. Therefore, PJE protects against blue-light-induced delayed corneal wound healing via its antioxidative, anti-inflammatory, and antiapoptotic effects mechanistically related to ROS production.